(NmESTOIMENIQ W QZYKE I RE^I (B/s - (NsELIWERSTOWA(B, (NoLXGA nIKOLAEWNAs; (NqRCEWA(B, (Nw(B.(Nn(B.s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 147-150s
(Nan sssr(B, (NiN(B-(NT QZYKOZNANIQs
Keywords: (NaNGLIJSKIJ QZYKs; (NgRAMMATIKAs; (NmESTOIMENIE W ANGLIJSKOM QZYKEs; (NmESTOIMENIE W RUSSKOM QZYKEs; (NrUSSKIJ QZYKs